Off-farm employment and agricultural specialization in China - Wang, Xiaobing; Huang, Jikun; Rozelle, Scott (China economic review, 2017)
While it is well known that China's off farm labor market is emerging rapidly, less is known about the effect of movement off the farm on the farming practices of those that have continued to farm. The overall goal of this paper is to analyze the effects of changes in China's off farm employment on one aspect of the performance of China's agricultural sector: the emergence of specialization in farming. To achieve this goal, we have three specific objectives. First, we document the changes in the flow of labor out of China's villages. Second, we examine how specialization in farming has changed over time. Third, we examine the association between off farm labor flows and specialization. Using panel data from a national representative data collected by the authors between 1999 and 2008, the analysis finds that off farm employment is indeed rising rapidly. At the same time, specialization is occurring off and on the farm. There is a strong and robust correlation between off farm employment and on farm specialization. The results imply that China's agriculture has responded dynamically to the modernization happening elsewhere in the economy. •More one-fifth of households in rural China worked solely off the farm and were not engaged in farming by 2008.•Overall between the early 2000s and the late 2000s, specialization in agriculture is occurring•Specialization effect in agriculture can help offset or attenuate the loss of labor effect.•Specialization in agriculture is identified by the number of crops and the share that each households allocates to the most important crop.